Assessing students’ knowledge and soft skills competency in the industrial training programme: The employers’ perspective - Lim, Khong Chiu; Mahat, Nor Idayu; Rashid, Basri; Abdul Razak, Norhanim; Omar, Hamimi (Canadian Center of Science and Education, 2016)
The importance of developing soft skills competency among students should be the priority of all the Higher Educational Institutions (HEIs) in order to ensure their graduates are marketable. Therefore, it is essential for HEIs to distinguish the knowledge and soft skill levels of their students so that strategies and intervention could be implemented to rectify their capabilities.The main purpose of this study is to evaluate the knowledge and soft skills competency from the employer’s viewpoints on the Universiti Utara Malaysia (UUM) students participating in the industrial training programme. A total of 438 employers from different industrial backgrounds had participated in this study.A questionnaire consisting of five dimensions of soft skills which are basic knowledge, communication skills, practical skills, leadership, and attitude was utilized to collect data. The results of this study indicate that the employers were satisfied with the knowledge and soft skills competency portrayed by UUM students in preparing themselves for the real work environment. The employers from the service sectors were satisfied with students’ performance in all dimensions of soft skills measured. However, employers from the factory and commerce sector perceived as moderate satisfaction for all dimensions of soft skills.Additionally, the employers of the factory and commerce sector assessed by giving the lowest satisfaction score for “hands-on” skills, but generally they satisfied with the students’ communication skills. The information gathered can provide important insights from the perspective of organizations which is valuable in improving the overall hard and soft skills competency for future professionals and managers.